(untitled) (Medico Legal Update, 2021)
Introduction: The tongue is being represented bilaterally in the motor homunculus of the brain. Tongue has been used as an effective interface to send signals to central nervous system. The purpose of this article is to review all articles related to tongue stimulation in neurological rehabilitation. Method: All studies including case studies, cohort studies, experimental studies and reviews, which dealt with tongue stimulation in neurological conditions during the period between 2010 and 2020, were included in the study. Results: Tongue Stimulation has been used effectively n rehabilitation for improving balance in patients with vestibular disorders, multiple sclerosis patients, spinal cord injury patients and stroke patients. Tongue Stimulation has also been used to improve motor recovery in stroke patients. Conclusion: Tongue stimulation becomes a novel mode of stimulation in inducing neuroplasticity and can be used in wide variety of neurological patients. Further researches needs to be done on the effect of tongue stimulation on upper extremity rehabilitation in stroke patients.